Traditional knowledge of medicinal plants among the Malay villagers in Kampung Mak Kemas, Terengganu, Malaysia - Ong, H.C.; Zuki, R.M.; Milow, P. (2011)
This study was carried out to assess the traditional knowledge on medicinal plants in a Malay village in Malaysia. It was carried out through face to face interviews with respondents and collection and identification of medicinal plants in the village. A total of 56 species of medicinal plants were recorded during a series of folk botanical surveys at a village at Terengganu, Malaysia. A majority of these species are herbaceous angiosperms, followed by trees and shrubs. The most common part of plant used in preparing herbal medicine is the leaves. More plants are used for general health, to treat dermatological complaints, reproductive system, abdominal problems and fever compared to other ailments. The most common method of preparation is poultice, followed by decoction and infusion. Thus, more medicinal plants are used topically than orally.